RESPONSE OF TURMERIC EXPLANT ON CYTOKININ AND AUXIN IN MURASHIGE AND SKOOG - Mita Indriani; Erni Suminar; Noladhi Wicaksana; Denny Sobardini; Sulistyaningsih Sulistyaningsih; Anne Nuraini; Nursuhud Nursuhud; Syariful Mubarok (Jurnal Penelitian Saintek, 2019)
This study was aimed at determining the concentration of several types of cytokinins and auxin for the induction of turmeric shoots in vitro. The research was conducted at the Tissue Culture Seed Technology Laboratory, Faculty of Agriculture, Padjadjaran University, Jatinangor. The study was conducted from October 2017 to February 2018. The source of planting material is in the form of shoots from the turmeric rhizome. The source of explants or planting material came from the field collected at the Tissue Culture Seed Technology Laboratory, Faculty of Agriculture, Padjadjaran University. Explants were taken from rhizome buds with a size of 0.6-2.0 cm. The experiment used a Completely Randomized Design which was analyzed using the Student’s T-test method. The number of experimental and control groups in this study were seven groups. Variation in treatment with different BAP, thidiazuron, zeatin, and NAA concentrations in each group. The results show that Thidiazuron 1 mgL-1 + NAA 1 mgL-1 gives better results on the percentage of live explants and number of shoots on turmeric plants (Curcuma domestica Val.) Clones 41 at the age of 14 weeks after planting.RESPONS EKSPLAN KUNYIT PADA SITOKININ DAN AUKSIN DALAM MEDIA MURASHIGE DAN SKOOGPenelitian ini bertujuan untuk mendapatkan salah satu konsentrasi dari beberapa jenis sitokinin dan auksin untuk induksi tunas kunyit secara in vitro. Penelitian dilakukan di Laboratorium Kultur Jaringan Teknologi Benih, Fakultas Pertanian, Universitas Padjadjaran, Jatinangor. Waktu pelaksanaan penelitian ini dimulai pada awal bulan Oktober 2017 sampai bulan Februari 2018. Sumber bahan tanam berupa tunas dari rimpang tanaman kunyit. Sumber eksplan atau bahan tanam berasal dari lapangan yang dikoleksi di Laboratorium Kultur Jaringan Teknologi Benih, Fakultas Pertanian, Universitas Padjadjaran. Eksplan diambil dari mata tunas rimpang dengan ukuran 0,6-2,0 cm. Percobaan menggunakan Rancangan Acak Lengkap yang dianalisis menggunakan metode Student’s T-test. Jumlah kelompok eksperimen dan kontrol dalam penelitian ini adalah tujuh kelompok. Variasi perlakuan dengan penambahan konsentrasi BAP, thidiazuron, zeatin, dan NAA yang berbeda pada setiap kelompok. Hasil penelitian ini menunjukkan bahwa Thidiazuron 1 mgL-1 + NAA 1 mgL-1 memberikan hasil yang lebih baik pada persentase eksplan hidup dan jumlah tunas pada tanaman kunyit (Curcuma domestica Val.) klon 41 pada umur 14 MST (Minggu Setelah Tanam).